Monboddo y Rousseau (1933) - Lovejoy, Arthur (Revista de Filosofía, 2007)
The work –here published for the first time in Spanish translation– presents the main theses maintained by Monboddo and Rousseau regarding the nature of higher primates. This subject-matter motivated a long and deep discussion throughout the 18th century, and triggered the first evolutionist intuitions later developed by Charles Darwin.